The Effect of Corporate Taxation and Ownership on Raising Shareholder Capital - Robert Krämer; Vilen Lipatov (Center for Economic Studies and ifo Institute (CESifo), 2013)
We analyze how interactions between corporate taxation and corporate governance affect shareholder capital. Using a model with strategic interaction between managers and outside shareholders, we hypothesize that, while an increase in the corporate tax rate decreases shareholder capital, an increase in tax enforcement attenuates this effect. The tax effect is less severe if firms have a more dispersed ownership structure. Empirically, using a large panel of European firm-level data, we find support for these hypotheses.
Keywords: G32; H25; H26; 330; corporate taxation; corporate governance; managerial diversion; shareholder capital; tax enforcement